9x-6x+6=x-9+15

Simple and best practice solution for 9x-6x+6=x-9+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-6x+6=x-9+15 equation:



9x-6x+6=x-9+15
We move all terms to the left:
9x-6x+6-(x-9+15)=0
We add all the numbers together, and all the variables
9x-6x-(x+6)+6=0
We add all the numbers together, and all the variables
3x-(x+6)+6=0
We get rid of parentheses
3x-x-6+6=0
We add all the numbers together, and all the variables
2x=0
x=0/2
x=0

See similar equations:

| 3x-12-x=5x+21 | | -43=-6+x-3 | | 2x=2x-24 | | -w+(4w+3)=-12 | | 1l+2l=96 | | X2+7x-12=0 | | n3=216 | | 5.4a+15=74.4 | | x+14/7=2 | | (x-12)3=-5+2x | | 3(x-2)-5(x-3)=-2- | | 4g+3​(-4+4​g)=1-g | | 5x+2.4=9.9 | | 7=a-(13) | | 2z-10=1/3(2-9) | | Y/1-y=2 | | x^2+x+7+2x-3=5x-4 | | -26=n-2 | | 7=x-1/x+2 | | 2(x-5)=3x+-9x+2/3 | | 0.27=3^x | | 5(3x12)=-15 | | x=3x+2x-16 | | 29=3+z | | 4y+3+2y+9=10y-8 | | 6(3n+3)=8(4n+2)+6 | | 4(x+3)=7x+12-3x | | 6x-6=32 | | 4x=(4x+3)2 | | 7v+23=4+8v-22 | | 2x2-9+4=0 | | -13k=-26 |

Equations solver categories